Faktor Kesulitan Siswa dalam Pembelajaran Bahasa Arab di MTs Al-Manar Medan - Arridho Prasetiyo Pradana P; Harun Al-Rasyid (EduInovasi: Journal of Basic Educational Studies, 2024)
This article explains the Factors of Student Difficulty in Learning Arabic at MTs Al-Manar Medan. This research is very important to carry out to find out the various factors that become obstacles for Mts Al-Manar Medan students in learning Arabic and find solutions. This study uses a qualitative method. Research participants were students of MTS Al-Manar Medan. Data collection methods and techniques were in the form of questionnaires distributed to students at Mts Al-Manar Medan and interviews conducted with several students and teachers teaching Arabic subjects. The findings from this research show that students’ difficulties in learning Arabic are influenced by five factors consisting of internal and external factors, namely, first, the students’ lack of memorizing Arabic vocabulary. Second, the lack of student interest in learning Arabic. Third, students come from various different elementary school educational backgrounds. Fourth, the teacher factor, which can be seen from teaching methods that are less attractive and the ability to manage the class that is not optimal. Fifth, environmental factors, for example the use of regional languages at home which is more dominant than Arabic